Research Advances and Detection Methodologies for Microbe-Derived Acetylcholinesterase Inhibitors: A Systemic Review - Su, Jingqian; Liu, Huiying; Guo, Kai; Chen, Long; Yang, Minhe; Chen, Qi (Molecules (Basel, Switzerland), 2017)
Acetylcholinesterase inhibitors (AChEIs) are an attractive research subject owing to their potential applications in the treatment of neurodegenerative diseases. Fungi and bacteria are major producers of AChEIs. Their active ingredients of fermentation products include alkaloids, terpenoids, phenylpropanoids, and steroids. A variety of in vitro acetylcholinesterase inhibitor assays have been developed and used to measure the activity of acetylcholinesterases, including modified Ellman’s method, thin layer chromatography bioautography, and the combined liquid chromatography-mass spectrometry/modified Ellman’s method. In this review, we provide an overview of the different detection methodologies, the microbe-derived AChEIs, and their producing strains.